Normal vitreous promotes angiogenesis via activation of Axl. Issue 1 (5th November 2020) - Wu, Wenyi; Xia, Xiaobo; Tang, Luosheng; Yao, Fei; Xu, Huizuo; Lei, Hetian
Abstract: Vitreous has been reported to prevent tumor angiogenesis, but our previous findings indicate that vitreous activate the signaling pathway of phosphoinositide 3‐kinase (PI3K)/Akt, which plays a critical role in angiogenesis. The goal of this research is to determine which role of vitreous plays in angiogenesis‐related cellular responses in vitro. We found that in human retinal microvascular endothelial cells (HRECs) vitreous activates a number of receptor tyrosine kinases including Anexelekto (Axl), which plays an important role in angiogenesis. Subsequently, we discovered that depletion of Axl using CRISPR/Cas9 and an Axl‐specific inhibitor R428 suppress vitreous‐induced Akt activation and cell proliferation, migration, and tuber formation of HRECs. Therefore, this line of research not only demonstrate that vitreous promotes angiogenesis in vitro, but also reveal that Axl is one of receptor tyrosine kinases to mediate vitreous‐induced angiogenesis in vitro, thereby providing a molecular basis for removal of vitreous as cleanly as possible when vitrectomy is performed in treating patients with proliferative diabetic retinopathy.